Reliability of the Installation and Operation of Pipeline Systems - Beden, S. M. (Basrah Journal for Engineering Sciences, 2016)
Pipelines are one of the most convenient and effective ways of transporting petrol over a long distance. The environment applies, beyond extremely high external pressures, low temperatures and intensive corrosive process, the occurrence of defects on the pipe body, which compromises the structural integrity of pipelines leading to catastrophic failures. The main modifications concern the mechanical resistance, toughness at low temperatures weld ability and resistance to embrittlement related to hydrogen. Among mechanical characteristics, the fracture toughness is very important for pipeline steels in design and safe assessment. Aiming to enhance the reliability and operation of complex pipelines system, a study based on the mechanics of the elastoplastic fracture in order to determine better prediction of the fatigue life. The materials tested here are API 5L X42 and X52 micro alloyed steels, as well as to evidence the toughness resistance of these materials. Results indicated that both X42 and X52 steel behave in a similar way and in all cases a slight increase of the transition temperature was found. The characteristic toughness value shows an evident loss in mechanical performances if compared to the uncharged one.